PENGEMBANGAN BUKU TEKS PEMBELAJARAN MENULIS TEKS NONSASTRA BERBASIS PENDEKATAN PROSES - Yuniar, Mustika Suci; Zuchdi, Darmiyati (Jurnal Pendidikan Bahasa dan Sastra, 2018)
This research aimed to: (1) develop nonfiction texts of writing learning textbook based on process approach for the eleventh grade of senior high school; (2) find out the quality of nonfiction texts of writing learning textbook based on process approach that has been developed; and (3) find out the effectiveness of nonfiction texts writing learning textbook based on process approach for the eleventh grade of senior high school. This research is research and development that refers to research and development model of Borg Gall. The development design included: (1) information collecting; (2) product development; (3) product testing; and (4) product revisions. Before the tryout, the textbook were validated by material and graphic experts, and practitioners. The data were collected using an interview guide, questionnaires, observation sheets, and test. The interview data in the infomation collecting stage and observation data in the implementation of the product were analyzed using the qualitative descriptive technique. The questionnaires data were analyzed using five scale score conversion. The t-test with a significance level of 0.05 was used to find out the effectiveness of the textbook.  The research finding revealed that the textbook which had been developed considered good with the percentage of quality 83.34% based on the questionnaire results analysis by the material and graphic experts, practitioner’s opinion, and student’s responses to the developed textbook.  Thus, it can be concluded that the nonfiction texts writing learning textbook based on process approach for the eleventh grade of senior high school was effectively used in nonfiction texts writing instruction.